Optimalisasi Manajerial Pengelolaan Dana Bantuan Sosial Selama Pandemi Covid 19 Didesa Sumberejo Mranggen Kabupaten Demak - Yusroni, Nanang; Irhamni, Ricza; Purnomo, Purnomo (Universitas Dian Nuswantoro, 2024)
The Sumberejo Village Office is tasked with carrying out government, development and community affairs, as well as carrying out public services in the field of Population Administration based on Demak Regency Regional Regulation Number 10 of 2014, one of which is serving community administration. During the PPKM period there were various obstacles in determining the target strategy for targeting poor people who would be given social assistance, so far the process of collecting data on poor families is currently carried out by each RT manually on writing paper, to then be given to Village staff, there are obstacles in processes related to the length of time each RT provides data information and preparing data recapitulation reports. Apart from that, there are other obstacles related to the process of determining the provision of poor funds because there is no simulation of the calculation method. By supporting decisions to provide funds for underprivileged communities using the Analytical Hierarchy Process (AHP) method which can later support determining assistance for the community. The criteria used in providing PKH funds are education, employment, income, status, age, residence, health and number of children.